Diagnosis and Treatment of Sinonasal Inverted Papilloma - Thapa, N (Nepalese Journal of ENT Head and Neck Surgery, 2011)
DOI: 10.3126/njenthns.v1i1.4737 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.30-33